The South China Sea International Disputes with the ASEAN Area (in International Maritime Law) - Aaron Leonardo Borte; Ong Argo Victoria (International Journal of Law Reconstruction, 2023)
In history, the sea has been shown to have had various functions, including as a source of food for mankind, as a trade highway, as a means of conquest, as a place for battles, as a place for fun and recreation, and as a means of unifying or separating nations. nation. As one of the regions with a high degree of heterogeneity, the Asia Pacific region is often considered a region that is very vulnerable to conflict on the basis of a fragile regional balance. The purpose of this study is to find out that one of the territorial conflicts in the Asia Pacific is the South China Sea conflict which involves several countries including China, Taiwan, the Philippines, Vietnam, Malaysia and Brunei Darussalam. This research uses a normative approach in accordance with international maritime regulations, especially UNCLOS and the UN Arbitration Council. The results of this study indicate that she said the South China Sea entered a new chapter by submitting a dispute over the issue of territorial claims to the Arbitration Court in The Hague, Netherlands. The Philippines in January 2013 has officially brought the territorial dispute in the South China Sea to the international arbitration body. Political disputes have been stopped and entered a new phase, namely legal settlement. The issue that arises is whether legal settlement can be the key answer to this territorial dispute, then whether legal settlement can create justice for the disputing countries. Furthermore, whether a legal settlement can dampen and create stability and security in the region. It may be very far if a legal settlement can fulfill some of the questions above.